Have Chinese Universities Hit a Plateau? - Usher, Alex (International Higher Education, 2018)
Top Chinese universities have grown to have enormous financial clout, rivalling that of some top American institutions. But their rapid rise may be coming to an end as their sheer size precludes further major increases. Scientific output at these universities is now very high, though there remains room to improve in terms of impact.